Economic sanctions in international arbitration - Vasylieva, Anastasiia (Riga Graduate School of Law, 2018)
Historically, economic sanctions, as options of foreign policy, are aimed on changing the behavior of the target state and its regime. In a very extreme situation, economic sanctions can be used in a comprehensive manner, which means prohibiting all kinds of financial transactions with the sanctioned state. The aforesaid policy necessarily constitutes a significant influence on the commercial relations between individuals within a sanctioned state and their international contractual relations. The imposed sanctions can cause obstacles for performing contractual obligations, s can lead to the disputes in international arbitration. Nowadays, the issue of sanctions in international arbitration has attracted a wide interest because of the recently established sanction regimes. The research is performed in the scope of international investment arbitration and international commercial arbitration.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Procedural law::Arbitration; International investment arbitration; International commercial arbitration; Economic sanctions